Ultra and Extremely Low Frequency Electromagnetic Fields - Surkov, Vadim; Hayakawa, Masashi (Springer Geophysics, 2014)
The major emphasis of this book is on physical mechanisms and sources of the ULF/ELF natural electromagnetic fields noises. In the course of this text, some of these mechanisms of magnetospheric origin will be treated in detail and others in a more sketchy fashion, while the global electromagnetic resonances excited by lightning activity and other sources are the priority. The interested reader is referred to the books cited in the text for details about the ULF/ELF fields of magnetospheric origin. Much emphasis is put on studies of electromagnetic phenomena caused by rock deformation/fracture including the ULF/ELF effects possibly associated with tectonic activity, earthquakes, and other natural disasters. One of the challenges of this research is to fully understand electromagnetic effects and physical processes in the rocks deep in the Earth's crust.